Integration of repositories in elearning systems - Leal, José Paulo (2015)
The wide acceptance of digital repositories today in the eLearning field raises several interoperability issues. In this paper we present the interoperability features of a service oriented repository of learning objects called crimsonHex. These features are compliant with the existing standards and we propose extensions to the IMS interoperability recommendation, adding new functions, formalizing message interchange and providing also a REST interface. To validate the proposed extensions and its implementation in crimsonHex we developed a repository plugin for Moodle 2.0 that is expected to be included in the next release of this popular learning management system.